2019
DOI: 10.1002/jcb.27851
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the long noncoding RNA HOTTIP inhibits cell proliferation and enhances cell sensitivity to cisplatin by suppressing the Wnt/β‐catenin pathway in prostate cancer

Abstract: Background: Prostate cancer (PCa) is a prevalent and deadly cancer worldwide. Considering the malignant progression and therapeutic resistance of PCa, further dissection of the underlying mechanisms and exploration of novel therapeutic targets for PCa are urgently needed. The long noncoding RNA HOTTIP has recently been revealed as an oncogenic regulator in different cancers; however, whether HOTTIP is involved in PCa remains poorly understood. Here, we examined the crucial roles of HOTTIP in the proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Cancer cells with a stem cell phenotype are more resistant to anti-cancer drugs and express higher levels of ABCG2 compared with those without stem cell phenotype (29)(30)(31). The activation of ABCG2 (32) or ABCB1 (31) is considered to be one of the mechanisms for drug resistance of CSCs. For instance, the presence of ABCG2 in certain populations of CSCs increases the likelihood of resistance to various anticancer drugs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells with a stem cell phenotype are more resistant to anti-cancer drugs and express higher levels of ABCG2 compared with those without stem cell phenotype (29)(30)(31). The activation of ABCG2 (32) or ABCB1 (31) is considered to be one of the mechanisms for drug resistance of CSCs. For instance, the presence of ABCG2 in certain populations of CSCs increases the likelihood of resistance to various anticancer drugs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, constitutive Wnt pathway activation is associated with tumor recurrence and poor prognosis in NSCLC patients [9,40,41,42,43,44,45]. The Wnt/β-catenin pathway has also been reported to play a key role in cisplatin resistance in various human cancer types, including lung cancer [46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61]. Cancer stem cells (CSCs) are associated with chemoresistance, and Wnt signaling is one of their regulators [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA HOXA distal transcript antisense RNA (HOTTIP) is strongly connected to cancer and has previously been reported to enhance tumor progression and chemoresistance [179]. Jiang et al [44] were the first to investigate HOTTIP's involvement in PCa chemoresistance. As reported, suppression of HOTTIP resulted in increased cisplatin sensitivity in the PCa cell lines DU-145 and PC-3 by inhibiting Wnt/β-catenin signaling [44].…”
Section: Hottipmentioning
confidence: 99%
“…Jiang et al [ 44 ] were the first to investigate HOTTIP’s involvement in PCa chemoresistance. As reported, suppression of HOTTIP resulted in increased cisplatin sensitivity in the PCa cell lines DU-145 and PC-3 by inhibiting Wnt/β-catenin signaling [ 44 ]. This corroborates a number of previous studies that found HOTTIP to promote chemoresistance in numerous cancer entities [ 180 , 181 , 182 ], including osteosarcoma in which the regulation of Wnt/β-catenin by HOTTIP was also described [ 182 ].…”
Section: Lncrnas and Drug Resistance In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation